2022
DOI: 10.1021/jacsau.2c00487
|View full text |Cite
|
Sign up to set email alerts
|

Base-Induced Dehydrogenative and Dearomative Transformation of 1-Naphthylmethylamines to 1,4-Dihydronaphthalene-1-carbonitriles

Abstract: Solvothermal treatment of 1-naphthylmethylamine with potassium hydride (KH) or n-butyllithium (n-BuLi)− potassium t-butoxide (t-BuOK) in THF induces unusual two consecutive β-hydride eliminations to form 1-naphthonitrile and KH. The freshly generated KH is hydridic enough to undergo dearomative hydride addition to the resultant 1-naphthonitrile regioselectively at the C4 position to afford α-cyano benzylic carbanion, which could be functionalized by a series of electrophiles, liberating the corresponding 1,4-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
0
2
0
2
Order By: Relevance
“…Besonders bemerkenswert ist die Umwandlung von 1‐Naphthylmethylamin in das 1,4‐Dihydronapthalin‐1‐carbonitril, bei der KH die Oxidation eines primären Amins zu einem Nitril erleichtert. Die wiederholte β‐Hydrid‐Eliminierung aus dem Kaliumsalz des Amid/Iminyl‐Anions wurde für die Bildung von Nitrilen verantwortlich gemacht [27] …”
Section: Figureunclassified
See 1 more Smart Citation
“…Besonders bemerkenswert ist die Umwandlung von 1‐Naphthylmethylamin in das 1,4‐Dihydronapthalin‐1‐carbonitril, bei der KH die Oxidation eines primären Amins zu einem Nitril erleichtert. Die wiederholte β‐Hydrid‐Eliminierung aus dem Kaliumsalz des Amid/Iminyl‐Anions wurde für die Bildung von Nitrilen verantwortlich gemacht [27] …”
Section: Figureunclassified
“…Die wiederholte β-Hydrid-Eliminierung aus dem Kaliumsalz des Amid/Iminyl-Anions wurde für die Bildung von Nitrilen verantwortlich gemacht. [27] Sukbok Chang (Korea Advanced Institute of Science and Technology & Institute for Basic Science) gab einen Überblick über die fast zehnjährige Erforschung der Verwendung von Dioxazolonen als Amidierungsreagenzien in übergangsmetallvermittelten CÀ N-Bindungsaufbauenden Reaktionen. [28] Durch eine Reihe grundlegender mechanistischer Studien wies seine Gruppe nach, dass diese Nitrenoidvorläufer mit Übergangsmetallen entweder über den Weg der inneren oder der äußeren Sphäre reagieren können.…”
unclassified
“…Particularly striking is the conversion of 1‐naphthylmetylamine into the 1,4‐dihydronapthalene‐1‐carbonitrile, where KH facilitates the oxidation of a primary amine to a nitrile. Repeated β‐hydride elimination from the potassium salt of the amide/imininyl anion was invoked to account for the formation of nitriles [27] …”
Section: Figurementioning
confidence: 99%
“…Repeated β-hydride elimination from the potassium salt of the amide/imininyl anion was invoked to account for the formation of nitriles. [27] Sukbok Chang (Korea Advanced Institute of Science and Technology & Institute for Basic Science) provided an overview of his group's nearly decade long exploration of the use of dioxazolones as amidating reagents in transitionmetal-mediated CÀ N bond-forming reactions. [28] Through a series of fundamental mechanistic studies, his group demonstrated that these nitrenoid precursors can react with transition metals either via inner-or outer-sphere pathways.…”
mentioning
confidence: 99%